Health Beliefs, Illness Perceptions, and Self-Management Behaviors in Hypertension Clients - Muhamad Jauhar; Ririn Widyasari; Heny Siswanti; Novi Tiara (Indonesian Journal of Health Research and Development, 2026)
Background: Hypertension is a health problem that impacts all age groups and social backgrounds, with the risk of serious complications, reduced quality of life, and a huge burden for clients, families, and the country. The increasing number of hypertension cases requires serious attention to reduce its impact.Aims: This study analyzes the relationship between health beliefs disease perceptions and self-management behavior in hypertensive clients at the Juwana Community Health Center.Methods: This research used a cross-sectional design and involved 95 clients selected using purposive sampling. Data was collected through a valid and reliable questionnaire and then analyzed using the Spearman-Rho correlation testResult: The results showed a significant relationship between health beliefs and self-management behavior (r = 0.327; p = 0.001), while the relationship between illness perception and self-management was insignificant (r = 0.178; p = 0.083). The majority of clients had sufficient categories for health beliefs (74%), disease perceptions (81.3%), and self-management behavior (71.9%).Conclusion: In conclusion, health beliefs influence self-management behavior, while illness perceptions do not have a significant relationship. Interactive media-based educational programs are needed to increase health confidence and support self-management of hypertension patients.